Groundwater contamination pathways of phthalates and bisphenol A: origin, characteristics, transport, and fate – A review. (December 2022) - Dueñas-Moreno, Jaime; Mora, Abrahan; Cervantes-Avilés, Pabel; Mahlknecht, Jürgen
Graphical abstract: Highlights: Sources, fate and occurrence of phthalates and BPA in aquifers have been reviewed. Phthalates and BPA have been globally detected in groundwater reservoirs. Landfills, sewage sludge and wastewater are the main sources to groundwater pollution. Some phthalate and BPA features and soil conditions promote the transport to aquifers. Worldwide guidelines values for drinking water vary in a wide range of concentrations. Abstract: Phthalic acid esters (PAEs) or phthalates and bisphenol A (BPA) are emerging organic contaminants (EOCs) that may harm biota and human health. Humans can be exposed to these contaminants by drinking water consumption from water sources such as groundwater. Before their presence in aquifer systems, phthalates and BPA can be found in many matrices due to anthropogenic activities, which result in long-term transport to groundwater reservoirs by different mechanisms and reaction processes. The worldwide occurrence of phthalates and BPA concentrations in groundwater have ranged from 0.1 × 10 −3 to 3 203.33 µg L −1 and from 0.09 × 10 −3 to 228.04 µg L −1, respectively. Therefore, the aim of this review is to describe the groundwater contamination pathways of phthalates and BPA from the main environmental sources to groundwater. Overall, this article provides an overview that integrates phthalate and BPA environmental cycling, from their origin to human reception via groundwater consumption. Additionally, in this review, the readers can use the information provided as a principal basis for existing policy ratification and for governments to develop legislation that may incorporate these endocrine disrupting compounds (EDCs) as priority contaminants. Indeed, this may trigger the enactment of regulatory guidelines and public policies that help to reduce the exposure of these EDCs in humans by drinking water consumption.